2008
DOI: 10.2217/17460794.3.2.167
|View full text |Cite
|
Sign up to set email alerts
|

The Influenza Matrix Protein 2 as a Vaccine Target

Abstract: Matrix protein (M)2 is an Influenza A, type III membrane protein with an extracellular domain (ectodomain of M2 [M2e]) of 23 amino acid residues, which is strongly conserved across virus strains. M2 fulfills an important biological function in the life cycle of the Influenza A virus and has been a target of antiviral drugs. M2e has generated much interest as a potential vaccine target, and a clinical M2e vaccine trial was initiated in 2007. The advantage of M2e compared with hemagglutinin, the prime antigen ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…For instance, it has been suggested that packaging signals are good targets for oligonucleotide-based inhibition (Giannecchini et al, 2009). In a similar vein, the M2 ectodomain has been proposed as a candidate immunogen for a 'universal' influenza vaccine, for which antigenic escape mutants will be less likely to develop because the M2e coding region is either congruent with or overlaps that of M1 (Saelens, 2008). We speculate that the fact that the first nine codons of the M2e coding region also overlap the segment 7 packaging signal (Gog et al, 2007;Hutchinson et al, 2008;Ozawa et al, 2009) will further constrain the development of escape mutants.…”
Section: Packaging Signals and Influenza Virus Evolutionmentioning
confidence: 99%
“…For instance, it has been suggested that packaging signals are good targets for oligonucleotide-based inhibition (Giannecchini et al, 2009). In a similar vein, the M2 ectodomain has been proposed as a candidate immunogen for a 'universal' influenza vaccine, for which antigenic escape mutants will be less likely to develop because the M2e coding region is either congruent with or overlaps that of M1 (Saelens, 2008). We speculate that the fact that the first nine codons of the M2e coding region also overlap the segment 7 packaging signal (Gog et al, 2007;Hutchinson et al, 2008;Ozawa et al, 2009) will further constrain the development of escape mutants.…”
Section: Packaging Signals and Influenza Virus Evolutionmentioning
confidence: 99%
“…Furthermore, M2e is highly expressed on infected cell surfaces and exhibits antigenic properties. Therefore, M2e-specific antibodies can bind to cells infected by the virus [19] . For this reason, the M2e peptide is considered to be an excellent tool for the diagnosis of influenza A virus [6].…”
Section: Introductionmentioning
confidence: 99%